(untitled) (Al-Aasar, 2026)
Neoliberalism has emerged as a dominant political and economic paradigm in contemporary societies, characterized by an emphasis on market rationality, deregulation, privatization, and the prioritization of capital accumulation. While these principles are often associated with economic growth, efficiency, and global competitiveness, a growing body of scholarship suggests that neoliberal governance may also reshape social norms and moral frameworks in ways that challenge fundamental ethical values. This study therefore examines the core principles and structural features of neoliberalism and critically analyses how neoliberal political and economic policies affect human welfare and the protection of human dignity.The research adopts a qualitative conceptual and analytical methodology, drawing on interdisciplinary literature from political economy, sociology, and ethical theory. Through a critical review and synthesis of key scholarly works on neoliberal governance and digital capitalism, the study explores the broader social and ethical implications of market-cantered policy frameworks.The analysis indicates that neoliberal policies frequently prioritize financial profitability and corporate expansion over concerns for social welfare and human dignity. In economic, social, and digital spheres, individuals are increasingly evaluated in terms of their market utility, contributing to the commodification of human experiences and social relations. Such developments normalize practices that may weaken ethical standards and social responsibility, generating socio-psychological and moral risks that conflict with enduring moral and religious principles.The study concludes that the unregulated expansion of neoliberal rationality poses significant challenges to the safeguarding of human dignity and calls for human-centered policy frameworks that balance economic development with ethical responsibility.